2021
DOI: 10.2147/imcrj.s307010
|View full text |Cite
|
Sign up to set email alerts
|

DYT6 Dystonia Mimicking Adolescent Idiopathic Scoliosis Successfully Treated by Pallidal Stimulation

Abstract: Purpose: Dystonia type 6 (DYT6) is an autosomal dominant monogenic movement disorder that often involves craniocervical and laryngeal regions, but can in rare circumstance present as trunk dystonia or severe scoliosis. Deep brain stimulation of the globus pallidus internus (GPi-DBS) has yielded favorable results in the treatment of DYT6 patients. This report describes the case of a 14-year-old male adolescent with DYT6 dystonia and severe scoliosis who was successfully treated by GPi DBS. Patients and Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…GPi DBS for medically refractory dystonia has been approved by the Food and Drug Administration in the United States since 2003, and two multicenter studies demonstrated clinical benefit in generalized dystonia since 2006 ( 15 , 16 ). Example images of GPi DBS placement for dystonia may be found here ( 17 ). For a review of its indications and uses, see ( 17 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GPi DBS for medically refractory dystonia has been approved by the Food and Drug Administration in the United States since 2003, and two multicenter studies demonstrated clinical benefit in generalized dystonia since 2006 ( 15 , 16 ). Example images of GPi DBS placement for dystonia may be found here ( 17 ). For a review of its indications and uses, see ( 17 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Example images of GPi DBS placement for dystonia may be found here (17). For a review of its indications and uses, see (17)(18)(19)(20). A 2021 systematic review of medically refractory dystonia of 35 studies (n = 319) found that GPi DBS placement was consistently safe and effective and noted that primary dystonias achieved better motor symptom and disability score improvement than secondary dystonias (21).…”
Section: Discussionmentioning
confidence: 99%